ELETRO-OXIDAÇÃO DE GLICEROL EM ELETRODOS DE Pt E PtRh EM MEIO ÁCIDO: ESTUDO DA VARIAÇÃO DE TEMPERATURA E DA COMPOSIÇÃO DOS CATALISADORES - Araujo, Herbert Rocha (2013)
The glycerol electrooxidation has been studied on smooth and high roughness platinum electrodes and PtRh electrodes in acid medium. The increasing temperature had have positive catalytic effect on bimetallic electrodes, but have been observed a negative effect to current stability. In same conditions the Pt electrodes have undergoes catalytic deactivation. In bimetallic electrodes the increasing of Rh until 10% had a positive effect on faradaic process in all temperatures. To high roughness platinum electrodes have been observed linear current with electrode area until temperature 55 °C. To other hand, a high current stability have been seen to intermediate roughness platinum electrode at room conditions. Spectroscope techniques showed us different reactional products like CO2, aldehdyes, carboxylic acids and possibility a cetone. Differences on intensity bands from CO2 showed us that Rh content less 10% favour at CO2 yielding with the potential and time.